2009
DOI: 10.1080/13504500902793481
|View full text |Cite
|
Sign up to set email alerts
|

Health and environmental sustainability indicators in Quang Tri Province, Vietnam

Abstract: Trieu Phong district, Dong Ha town and Huong Hoa district are in Quang Tri Province (central Vietnam). These areas were selected as case studies for analysis of sustainable development. Sixteen indicators of two dimensions of sustainable development were defined: eight health and eight environmental. The evolution of these indicators during the period 2000-2005 was analysed using available data in the provincial information bank, UN guidelines and expert discussions. It was found that all, except the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The results Percent of population living below poverty line (1), unemployment rate (2), mortality rate under age (3), nutritional rate status of five (4), life expectancy at birth (5), number of household with adequate disposal sewage facilities (6), percent of population with access to safe water (7), percent of population with access to primary health care facilities (8), immunization against infectious childhood diseases (9), natural growth rate (11), number of reordered crimes per 10,000 population (13), children reaching grades 5 of primary education (14), children reaching grades 9 of secondary education (15), children reaching grades 12 of primary education (16) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results Percent of population living below poverty line (1), unemployment rate (2), mortality rate under age (3), nutritional rate status of five (4), life expectancy at birth (5), number of household with adequate disposal sewage facilities (6), percent of population with access to safe water (7), percent of population with access to primary health care facilities (8), immunization against infectious childhood diseases (9), natural growth rate (11), number of reordered crimes per 10,000 population (13), children reaching grades 5 of primary education (14), children reaching grades 9 of secondary education (15), children reaching grades 12 of primary education (16) …”
Section: Discussionmentioning
confidence: 99%
“…First, the Delphi approach is used to select indicators for SD [5]. Then, the analytic hierarchy process (AHP) is used to analyse SD [6]. In these studies, the data are simply calculated in an Excel environment and/or analysed manually.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, Bartzas and Komnitsas (2020) designed an environmental AHP model to identify the most sustainable agricultural management practices at regional level whilst Tzouramani, Mantziaris, and Karanikolas (2020) examined the sustainability performance at the farm level. In a similar vein, Hai, Hai, Y, and Hens (2009) used the AHP approach to analyse 16 health and environmental indicators of sustainable development in a central province in Vietnam and found that this development was weak during the 2000–2005 period. Nevertheless, one can see that those studies pay more attentions to the sustainability performance of the agriculture sector and thus focus on the outcomes of the examined farms, for example, how high is the economic revenues that farmers receive or what are the environmental impacts of farming.…”
Section: Introductionmentioning
confidence: 99%
“…Towards sustainable development, minimizing climate change impacts, researchers have used a variety of approaches to sustainable development across a range of areas. To date, several assessment methods have been proposed and applied in order to establish the Sustainable development indicators (SIs) to measure the sustainable development, including DPSIR framework [2], Rapfish method [3], socio-ecological system framework [4], Z-score technique [5], Delphi method [6][7][8]. Recognizing the need for sustainability assessment in Vietnam, the Prime Minister issued a statistical indicator system with 28 economic-social-environmental indicators combined with more than 15 specific indicators for specific regions including Northern midlands and mountainous, Delta, Coastal, Centrally-run city and Countryside in Decision No.…”
Section: Introductionmentioning
confidence: 99%